An Experimental Study on the Achievement and Enhancement of Eighth Grade Students' Creative and Imitative Reasoning through Resource-Based Learning in Mathematics - Susilawati, Intan; Suhendra, Suhendra (PRISMA, 2025)
Creative and imitative reasoning are essential components of mathematics learning that support higher-order thinking skills. This study aims to examine the achievement and improvement of creative and imitative reasoning among eighth-grade students through the implementation of Resource-Based Learning (RBL). The research was conducted using a quasi-experimental method with a one-group pretest-posttest design. The subjects were 43 eighth-grade students from a junior high school in Indonesia, selected using purposive sampling based on prior mathematical ability. The sample was categorized into high (8 students), medium (20 students), and low (15 students) ability groups. Research instruments included a mathematical reasoning test, classroom observation, and interviews. The results showed differences in the achievement of creative and imitative reasoning among the three groups. High-ability students demonstrated better comprehension and problem-solving skills, whereas medium- and low-ability students struggled with complex tasks and abstract concepts. RBL was found to significantly enhance creative reasoning, particularly through active exploration and the use of diverse strategies. However, some students, especially from the low-ability group, continued to exhibit imitative thinking patterns. These findings suggest the need for a more structured and exploratory RBL design to further develop students’ independent and innovative thinking in mathematics.